Discourse Markers in Closed-Door Interview of 71st Miss Universe - Siburian, Tupa Parulian; Ginting, Immanuel Prasetya (Universitas Negeri Medan, 2024)
Discourse Markers (DMs) are indispensable elements in spoken communication, aiding in establishing coherence and organizing discourse in both textual and verbal interactions, as delineated by Brinton (2017). The objective of this research is to delineate the functions, and occurrences of Discourse markers employed by the finalists of the 71st Miss Universe 2022. This study employs a qualitative descriptive design to analyze the frequency and context of discourse markers based on the recorded video interviews of the contestants, employing Brinton's (1996) theory as the analytical framework. Additionally, the analysis of the data reveals the types and functions used, and their effects on conversation. the researcher found sixty-tree data which contain 128 DMs that consist of nineteen types. All these findings are not having the same function.